ANALISIS USAHA TATANIAGA KOPRA DALAM MENINGKATKAN PENDAPATAN KELUARGA DI DESA OENGKAPALA KECAMATAN WAKORUMBA UTARA KABUPATEN BUTON UTARA - Makmur Kambolong (Journal Publicuho, 2018)
his study aims to determine the system of trade in copra business in increasing family income and to find out the obstacles faced by copra craftsmen in increasing family income in the village of Oengkapala, North Wakorumba District, North Buton Regency. Data collection techniques are carried out by means of library research and field research using interview methods, documentation, and observation.Based on the results of the research, the copra marketing channel in the study area has 2 trading channels, a channel I, starting from producers to collecting traders to consumers and channel II starting from producers directly to consumers. Both of these channels have the same goal of distributing copra to consumers. The trading channel used by copra craftsmen in Oompala Village prefers to market their copies through marketing institutions from copra craftsmen to collectors. this can be seen from the five informants that the copra agreement that sold its copy to the collector traders reached 80% while the one who sold the copy to the large traders only reached 20%. the reason copra craftsmen sell their copies to collector traders is the number of marketing costs and lack of transportation. so copra craftsmen. The analysis of the increase in income of copra craftsmen in the village of Oasanala in the harvest season I was less increased while the harvest season II was in the category of increase. In the five selected informants, the copra craftsmen all experienced an increase in income during the second harvest season. because the income of copra crafters is due to, among other things, the difference in the selling price of copra and the difference in the amount of copra production from each coconut harvest season to copra. Keywords : Trading, Income